Academic Senate Minutes 2011-10-13 - Academic Senate:::::::::
Request from S&F to waive by-law rules to hold election approved. From SDS: Regarding the Subsidization of the new CAPS Student Fee for Pell Grant Students – First Reading completed. Revision to Grade Appeal, Student Grievance and Cheating and Plagiarism policies – First Reading completed.